Eggshell Pigment Composition Covaries With Phylogeny But Not With Life History Or With Nesting Ecology Traits Of British Passerines - Brulez, Kaat; Mikšík, Ivan; Cooney, Christopher R.; Hauber, Mark E.; Lovell, Paul George; Maurer, Golo; Portugal, Steven J.; Russell, Douglas; Reynolds, Silas James; Cassey, Phillip (My University, 2016)
No single hypothesis is likely to explain the diversity in eggshell coloration and patterning across birds, suggesting that eggshell appearance is most likely to have evolved to fulfill many nonexclusive functions. By controlling for nonindependent phylogenetic associations between related species, we describe this diversity using museum eggshells of 71 British breeding passerine species to examine how eggshell pigment composition and concentrations vary with phylogeny and with life-history and nesting ecology traits. Across species, concentrations of biliverdin and protoporphyrin, the two main pigments found in eggshells, were strongly and positively correlated, and both pigments strongly covaried with phylogenetic relatedness. Controlling for phylogeny, cavity-nesting species laid eggs with lower protoporphyrin concentrations in the shell, while higher biliverdin concentrations were associated with thicker eggshells for species of all nest types. Overall, these relationships between eggshell pigment concentrations and the biology of passerines are similar to those previously found in nonpasserine eggs, and imply that phylogenetic dependence must be considered across the class in further explanations of the functional significance of avian eggshell coloration.
Kolísání složení pigmentu vaječných skořápek s fylogenezí, ale ne s životním cyklem nebo s ekologickými rysy hnízdění Britských pěvců
Keywords: Biliverdin; Eggshell Coloration; Eggshell Ppigment; Phylogeny; Protoporphyrin; Biliverdin; Zbarvení vaječných skořápek; Pigmanty skořápek; Fylogeneze; Protoporfyrin